Wits and Interpretation : Keyboard Thoughts. - Edlund, Bengt. (Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2023)
This book offers critical demonstrations of various methods and concepts currently used in music analysis. Among the subjects are musical implications, tonal analysis, generative theory, ambiguity, similarity, and the key criteria met with in lawsuits of plagiarism. Finally, can a composer's sexual leanings be derived from his music?.